(3CMcGe GdeUGOQI ai GdbGfhf GdLfGFj (B:s "(3OQGSI ebGQfI(B" /s - (3eMehO fGLi eMeO MSfs; (3TQja SjO cGeds; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2022)
(3Ef GdYbhHI gi LRGA jaQV HGSe GdeLJeY Ydi TNU NGda CeQ GdTGQY, HfGkA Ydi Mce bVGFi UGOQ ef eMceI eNJUI, GdZQV efgG GdQOY HfhYjg GdYGe hGdNGU, aGdChd hgh efY hbhY GdLQjeI aj GdeSJbHd, hGdKGfi gh YOe YhOI GdLGfi Edi GdLQjeI eQI CNQi(B. (3hdbO MQUJ GdCOjGf GdSeGhjI, hSGjQJgG GdGJaGbjGJ GdOhdjI hGdbhGfjf GdhVYjI, HGdfU Ydi JWHjb GdeUGOQI aj LQGFe eYjfI, LeYJ eG Hjf GdYbhHI hGdJOGHjQ GdGMJQGRjI aVdG YeG bO jMce Hg cJYhjV dVMGjG GdLQjeI YeG dMbge ef VQQ LQGA GdLQjeI(B. (3aZfqj Yf GdHjGf Cf HYV GdLQGFe dgG WHjYI NGUI dG JcJaj GdbhGfjf GdhVYjI HJWHjb GdYbhHI GdCUdjI dgG, dPG CaQOJ dgG YbhHGJ EVGajI JcejdjI JbJVjgG MeGjI GdeUdMI GdYGeI hhVYJ ddYbhHI GdJcejdjI CMcGeG dJWHjbgG(B. (3hddeUGOQI WHjYI NGUI, efgG eG gh LhGRi hBNQ hLhHi(B: (3aGdChdi bO jMce HgG cYbhHI, CeG GdKGfjI JWHb Ydi LQGFe eYjfI, deG JeKdI ef NWQ Ch VQQ hgi GdJOGHjQ GdGMJQGRjI, hbO jMce HgG cJYhjV EPG hbYJ Ydi CTjGA ZjQ oeLQeI(B. (3hbO fU GdeTQY aj bhGfjf NGUI, Ydi hLhHjI GdeUGOQI ddCTjGA GdeHGM GdJYGed ajgG, hef gPG GdbHjd eUGOQI GdCehGd GdeJMUdI Ch GdCOhGJ hGdBdGJ hhSGFd Gdfbd GdeSJNOeI aj GQJcGH LQjeI, aVdG Yf GdCTjGA GdJi ef TCfgG Cf oJSJNOe aj GQJcGH LQGFe(B.s
Punishment is a penalty imposed in the name of society on a person who violates the order of the street, based on a judicial ruling issued by a competent court, the purpose of which is deterrence in both its public and private forms. The heavenly religions, along with international conventions and man-made laws, were keen to stipulate the application of confiscation in certain crimes, combining punishment and precautionary measures, as well as what may be decided as compensation for crime victims for the damage they suffered as a result of the crime. It goes without saying that some crimes have a special nature. Man-made laws are not satisfied with the application of the original punishment for them, so they have additional, complementary penalties required to protect the public interest, and provisions for the complementary punishment have been established for their application. Confiscation has a special nature, including what is permissible and the other obligatory: the first may be judged as a punishment, while the second is applied to certain crimes, because of the danger or harm they pose, which are precautionary measures, and it may be judged as compensation if it occurs on non-criminal things. In special laws, the legislator has stipulated the obligation of confiscation of things permissible to deal in, such as confiscation of funds obtained or tools, machines and means of transportation used in committing a crime, as well as things that would be used in committing crimes.
(3CWQhMI (B((3OcJhGQg(B)-(3LGeYI GdbGgQI(B-(3cdjI GdMbhb(B-(3bSe GdbGfhf GdLfGFj, (B2022s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI(B.447-500s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdLfGFjs; (3hbhY GdLQjeI aj GdeSJbHds; (3GdYbhHI hGdJOGHjQ GdGMJQGRjIs; (3hLhHjI GdeUGOQI ddCTjGAs; (3GdeUGOQIs; (3GdZQGeIs; (3GdeUGOQI hGdQOs; (3GdeUGOQI GdYGeIs; (3GdeUGOQI GdNGUIs; (3GdeUGOQI ai Gdabg GdGSdGeis; (3GdeUGOQI GdGMJQGRjIs; (3GdeUGOQI GdJYhjVjIs; (3GdeVHhWGJs; (3efGRYGJ GdJfajPs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs